Бадиий матнда синонимнинг қўлланиши : Бадиий матнда синонимнинг қўлланиши - Donishova Gulro'y, A (FILOLOGIYA UFQLARI JURNALI, 2024)
Annotation: This article focuses on one main tools for ensuring the diversity of artistic discourse, the ability to use synonyms as an important means of expression in language.